Aviation communication challenges and language training development: Perspectives from pilots and air traffic controllers - Haryani Hamzah; Pramela Krish; Afendi Hamat (Peoples' Friendship University of Russia (RUDN University), 2023)
Having error-free communication in air-to-ground communication is somewhat nonsensical in real-life conditions. Multiple factors, external or internal, inevitably cause miscommunication or misunderstanding. During unprecedented situations, the ability to adapt and language competency becomes a significant factor in ensuring that communication between pilots and air traffic controllers can succeed. Aviation English falls under English for Specific Purposes and acts as a lingua franca for aviation communication. Thus far, language training is still inadequate to prepare pilots and air traffic controllers during emergencies or non-routine situations. The open-ended survey was conducted before the first development phase of the aviation communication competence framework. The rationale of this survey is to understand the need and perception of aviation language among pilots and air traffic controllers. The findings suggest that although they feel confident using aviation English in radiotelephony, most agree that it is imperative to have language training to improve aviation communication safety and standardise aviation phraseology and language. The findings also suggest that fundamental English language proficiency and non-standard phraseology use reduce efficiency in aviation communication. Furthermore, cultural and linguistic diversity among pilots and air traffic controllers creates misunderstandings and non-understanding in interactions. These findings suggest that aviation language development and training can be improved by diligent monitoring and evaluating the current needs of pilots and air traffic controllers.